Melatonin attenuates chronic cough mediated by oxidative stress via transient receptor potential melastatin-2 in guinea pigs exposed to particulate matter 2.5 - Ji, Zhenjun; Wang, Zhen; Chen, Zhe; Jin, Hao; Chen, Chen; Chai, Senlin; Lv, Haining; Yang, Ling; Hu, Yakun; Dong, Rong; Lai, Kefang (Physiological research, 2018)
The aim of this study was to investigate the effects of melatonin on oxidative stress, the expression of transient receptor potential melastatin-2 (TRPM2) in guinea pig brains, and the influence of melatonin on oxidative stress in lungs and airway inflammation induced by particulate matter 2.5 (PM2.5). A particle suspension (0.1 g/ml) was nasally administered to the guinea pigs to prepare a PM2.5 exposure model. Cough frequency and cough incubation period were determined through RM6240B biological signal collection and disposal system. Oxidative stress markers, including malondialdehyde (MDA), total antioxidant capacity (T-AOC), total superoxide dismutase (T-SOD), and glutathione peroxidase (GSH-Px), in the medulla oblongata were examined through spectrophotometer. Reactive oxygen species (ROS) were detected in the hypoglossal nucleus, cuneate nucleus, Botzinger complex, dorsal vagal complex, and airway through dihydroethidium fluorescence. Hematoxylin-eosin (HE) staining and substance P expression via immunohistochemistry revealed the inflammatory levels in the airway. TRPM2 was observed in the medulla oblongata through immunofluorescence and Western blot. The ultrastructure of the blood-brain barrier and neuronal mitochondria was determined by using a transmission electron microscope. Our study suggests that melatonin treatment decreased PM2.5-induced oxidative stress level in the brains and lungs and relieved airway inflammation and chronic cough. TRPM2 might participate in oxidative stress in the cough center by regulating cough.
Keywords: oxidační stres; Blood-Brain Barrier; antioxidancia; Male; Medulla Oblongata; Particle Size; Guinea Pigs; pevné částice; Particulate Matter; plíce; medulla oblongata; mužské pohlaví; melatonin; kationtové kanály TRPM; látky znečišťující vzduch; Melatonin; Lung; Cough; Animals; Antioxidants; zvířata; velikost částic; mozek - chemie; morčata; Brain Chemistry; TRPM Cation Channels; Oxidative Stress; kašel; hematoencefalická bariéra; Air Pollutants